(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
Today, despite the advances in treatment and prevention, the problem of ARF remains relevant among pediatricians and otolaryngologists. Rheumatic carditis, complicated by ARF, is considered the main reason for hospitalization of patients aged 5 to 24 years in cardiology departments. Worldwide, every year, according to WHO statistics, about 500 thousand people fall ill with rheumatic fever, and in 300 thousand of them, ARF is complicated by the development of heart defects. These complications are the main cause of disability. As we know from foreign literature sources, the etiology of the development of ARF is GAS, but unfortunately the epidemiology of this infection has changed significantly in recent years. Today, the outdated term “rheumatism”, which traditionally previously belonged to the branch of rheumatology, has fallen out of use. And instead of this term, according to the classification, we still use the term “acute rheumatic fever”, which is most justified. The use of the term acute rheumatic fever directs the doctor to clarify the role of GABHS infection in the development of this pathology, and also indicates the need to prescribe antibiotics to eradicate the pathogen in the acute period (primary prevention) and prevent repeated attacks (secondary prevention). According to the ICD-X revision (WHO, Geneva, 1995), ARF belongs to class IX - “diseases of the circulatory system”, presented in headings I00 and I05 as independent groups of diseases and identified as independent nosological forms. This seems justified from the point of view of treatment tactics for patients and to justify primary and secondary prevention.